Taxonomic reevaluation of Pimpinella adiyamanensis and Pimpinella tunceliana (Apiaceae) - Akpulat, Huseyin Askin (Phytotaxa, 2025)
Pimpinella adiyamanensis was recently described from Adıyaman, Turkey, and P. tunceliana from Tunceli, Turkey. A detailed morphological assessment, including comparisons with type specimens and herbarium materials, indicates that P. adiyamanensis is conspecific with Tordylium hasselquistiae, while P. tunceliana is conspecific with P. kotschyana. Furthermore, field investigations confirmed that the type specimens of these taxa were collected from overlapping localities. Based on these findings, P. adiyamanensis is synonymized under T. hasselquistiae, and P. tunceliana under P. kotschyana.